Kepastian Hukum Dan Keadilan Dalam Penerapan Restorative Justice Pada Tahap Persidangan Pidana - bagus erlangga (Legalita, 2026)
This study examines the application of restorative justice in criminal trials, focusing on the tension between legal certainty and substantive justice within the Indonesian criminal justice system. This study is motivated by developments in modern criminal legal thought that position restorative justice as a progressive alternative to the retributive approach, which tends to disregard the interests of victims. The objective of this study is to analyze the guarantee of legal certainty in the application of restorative justice during the trial phase and to assess the extent to which its implementation has fulfilled the principles of justice for both victims and offenders. This study employs a normative legal methodology with a qualitative approach, utilizing legislative, conceptual, and philosophical perspectives. Data sources consist of primary legal materials in the form of legislation, as well as secondary legal materials in the form of scientific literature and previous research findings. The research hypothesis states that although restorative justice has the potential to realize substantive justice, its application in court proceedings is not yet supported by adequate legal certainty due to regulatory fragmentation and the absence of clear procedural guidelines. The research findings indicate that restorative justice has not yet been systematically integrated into the trial process, leading to inconsistencies in judicial practice and reliance on judicial discretion. Although this approach offers a more humanistic and participatory model of justice, there is a risk of pressure on victims as well as the potential for inconsistencies in the application of the law. This study contributes to the development of criminal law by emphasizing the importance of harmonizing regulations and establishing a clear legal framework to balance legal certainty and substantive justice. The significance of this study lies in its efforts to promote policy reform and strengthen the legitimacy of restorative justice within the formal criminal justice system.